Arabidopsis LORELEI, a Maternally Expressed Imprinted Gene, Promotes Early Seed Development. Issue 2 (15th August 2017) - Wang, Yanbing; Tsukamoto, Tatsuya; Noble, Jennifer A.; Liu, Xunliang; Mosher, Rebecca A.; Palanivelu, Ravishankar
Abstract : LORELEI expression in the seed is paternally silenced, and the maternal expression is critical for early seed development. Abstract: In flowering plants, the female gametophyte controls pollen tube reception immediately before fertilization and regulates seed development immediately after fertilization, although the controlling mechanisms remain poorly understood. Previously, we showed that LORELEI ( LRE ), which encodes a putative glycosylphosphatidylinositol-anchored membrane protein, is critical for pollen tube reception by the female gametophyte before fertilization and the initiation of seed development after fertilization. Here, we show that LRE is expressed in the synergid, egg, and central cells of the female gametophyte and in the zygote and proliferating endosperm of the Arabidopsis ( Arabidopsis thaliana ) seed. Interestingly, LRE expression in the developing seeds was primarily from the matrigenic LRE allele, indicating that LRE expression is imprinted. However, LRE was biallelically expressed in 8-d-old seedlings, indicating that the patrigenic allele does not remain silenced throughout the sporophytic generation. Regulation of imprinted LRE expression is likely novel, as LRE was not expressed in pollen or pollen tubes of mutants defective for MET1, DDM1, RNA-dependent DNA methylation, or MSI-dependent histone methylation. Additionally, the patrigenic LRE allele inherited from these mutants was not expressed in seeds. Surprisingly, and contrary to the predictions of the parental conflict hypothesis, LRE promotes growth in seeds, as loss of the matrigenic but not the patrigenic LRE allele caused delayed initiation of seed development. Our results showed that LRE is a rare imprinted gene that functions immediately after double fertilization and supported the model that a passage through the female gametophyte establishes monoalleleic expression of LRE in seeds and controls early seed development.